Wheat policy, wheat yield and production in Ethiopia - Zewdie Habte Shikur (Cogent Economics & Finance, 2022)
One of Ethiopia's main challenges is increasing wheat production and productivity by designing and implementing an appropriate wheat policy. The country has a wheat supply and demand gap, forcing the country to spend a substantial amount of foreign currency for wheat imports, which are primarily derived from coffee and oilseed exports. The increasing imbalance between supply and demand for wheat presents serious policy issues. The purpose of this study was to evaluate the effects of wheat policy, and wheat processing industrial policy on wheat yield and production using Vector Error Correction (VEC) and Tobit models. The comparative use of both Tobit and vector error correction models enables useful critiques of the applicability of both models. The models' results indicated that wheat policy had significant and positive effects on wheat yield and production. Importantly, the sign of the estimated coefficients is consistent across the models (i.e., Tobit and VEC models). More specifically, the estimated coefficients for technical change, market coordination, and integrated wheat policy interventions were positive, thereby confirming that the implementation of wheat policy interventions would significantly increase wheat production and productivity. Wheat yield and production were elastic due to policy interventions in the long run (i.e., elasticities values of wheat yield and output are greater than 1.00 unit). The results imply that wheat policy is important to increase wheat production and productivity by increasing the level of adoption of wheat technologies that shift from inelasticities to elasticities of wheat yield and production due to changes in the demand and price incentive in the long-run. The current supply-demand gap in wheat was 44%. In the long run, if the government implements the suggested wheat policy initiatives, this disparity might be decreased from 44 to 7%.
Keywords: 330; wheat policy; wheat processing industrial policy; wheat yield; wheat production